Promoting online teaching through active learning strategies: applications and innovations - Rakha, Ahmed Hassan (Frontiers in Education, 2025)
Online teaching extends beyond the mere creation of educational materials and the broadcasting of lectures. It should be enjoyable, engaging, collaborative, and comfortable, which can be achieved through the implementation of active learning strategies in an online environment. Therefore, this study focused on the effectiveness of online active learning techniques—think-pair-sharing, timed pair sharing, three-step interviews, jigsaw, and case studies—on students' cognitive achievement and attitudes toward online learning. The study involved 23 female students enrolled in the “Methods of Teaching Physical Education (PE) and Self-Defense Sports” e-course. A quasi-experimental method was employed, creating a single group in which blackboard e-learning systems were utilized alongside online active learning strategies. A repeated-measures ANOVA was conducted to assess the effect size across pre, post, and follow-up tests. The results revealed significant differences between the pre- and post-measurements, with the post-measurements demonstrating greater effectiveness. The follow-up measurement indicated statistically significant differences compared with the premeasurement measurement (η2 = 0.98). Despite a one-month interruption without learning or teaching, there was no statistically significant difference between the follow-up and post-measurements, suggesting that the experimental group maintained their cognitive level. Furthermore, the results indicated that students' positive attitudes toward active online learning strategies influence cognitive, emotional, and behavioral factors. In conclusion, these techniques improve information processing and working memory in online courses, enhancing cognitive outcomes, motivation, and skills for academic success. This paper advocates transforming traditional online learning into interactive, student-centered experiences that foster critical thinking and retention. Successful implementation requires careful planning, resources, and skilled educators.